ESTETIKA DALAM NOVEL JATISABA KARYA RAMAYDA AKMAL - Sugiarti, Sugiarti (LITERA, 2016)
This study aims to describe: (1) the uniqueness of esthetic codes as a means to express events, and (2) forms of social esthetics in Jatisaba, a novel by Ramayda Akmal. It employed the stylistic approach focusing on the linguistic system analysis of literary works and interpretations to obtain holistic meanings. The data source was Jatisaba. The data were analyzed by: (1) descriptive technique, (2) hermeneutic understanding, and (3) interactivedialectic technique. The findings are as follows. First, the uniqueness of esthetic codes in Jatisaba is characterized by the use of language as an aesthetic means. The selection of appropriate figures of speech is capable of expressing characters' experiences. Second, the social esthetics is described through the use of words or sentences related to sociocultural aspects to provide beauty nuances.